The Contagion of Donation Behaviors Changes Along With the Abatement of the COVID-19 Pandemic: An Intertemporal Survey Experiment - Li, Shuaiqi; Liu, Xiaoli; Li, Jianbiao (Frontiers in Psychology, 2021)
We conducted an intertemporal online experiment to examine the contagion of others’ positive and negative donation behaviors. We collected two sets of data during and after the peak of the COVID-19 pandemic in China. The participants donated to the charitable fund, “Against COVID-19, The China Charity Federation Is on the Move.” We further investigated the mediating effect of social anxiety on the link between the contagion of donation behaviors and the changes in the COVID-19 situation. A total of 1022 participants (Mage = 22.68, 63.01% females) participated in the intertemporal online experiment and were considered in the statistical analyses. Our findings were as follows. First, the donation behaviors of others significantly changed these participants’ initial donation decisions, with increased or decreased donation amounts being associated with a positive or negative donation behavior, respectively. Others’ positive donation behavior was more likely to nudge these participants into changing their initial decisions (31.82%, Mean = 15.177, SD = 1.586) than negative donation behavior (18.28%, Mean = 12.122, SD = 1.908) during the peak of the pandemic. However, such difference disappeared after the peak because the contagion of positive donation behavior significantly decreased along with the abatement of the pandemic. Second, the participants’ social anxiety decreased along with the abatement of the pandemic, and social anxiety completely mediated the relationship between the pandemic abatement and the decrease in the contagion of positive donation behaviors. These findings advance our understanding of the motivations and influence mechanism of individuals’ donation decisions in the current pandemic situation and help make informed policy making decisions.